Generation of Hepatocytes and Nonparenchymal Cell Codifferentiation System from Human-Induced Pluripotent Stem Cells - Ying Shi; Jiali Deng; Xiaopu Sang; Yihang Wang; Fei He; Xiaoni Chen; Anlong Xu; Fenfang Wu (Hindawi Limited, 2022)
To date, hepatocytes derived from human-induced pluripotent stem cells (hiPSC) provide a potentially unlimited resource for clinical application and drug development. However, most hiPSC-derived hepatocyte-like cells initiated differentiation from highly purified definitive endoderm, which are insufficient to accurately replicate the complex regulation of signals among multiple cells and tissues during liver organogenesis, thereby displaying an immature phenotypic and short survival time in vitro. Here, we described a protocol to achieve codifferentiation of endoderm-derived hepatocytes and mesoderm-derived nonparenchymal cells by the inclusion of BMP4 into hepatic differentiation medium, which has a beneficial effect on the hepatocyte maturation and lifespan in vitro. Our codifferentiation system suggests the important role of nonparenchymal cells in liver organogenesis. Hopefully, these hepatocytes described here provide a promising approach in the therapy of liver diseases.